O bordado-devir nos processos formativos - Spineli, Patrícia Mangili Juliani (Universidade Federal de São Carlos, 2021)
This paper presents the result of an investigation that started from the following question: what relationships can be established between embroidery and teacher education? The work begins with a memorial, through which the researcher seeks to understand the origin of this concern and how it relates to embroidery, so present in the personal and professional processes of being a woman-teacher-researcher. After the memorial, in which the memory is defined as a sustaining frame, the work presents the mapping of theses and dissertations catalogued in the CAPES platform, as a research methodology called state of knowledge, in order to identify how embroidery is guided in the universe of academic productions already concluded within the field of Education, in the research line Teacher Education. And, based on this survey, propose a weaving with the literature to weave possible paths with the results brought by the works found and to look for probable paths beyond them. Simultaneously, an embroidered cartography of the research writing process, in a rhizomatic training trajectory, with lines of escape, resistance, and support, is being built. A research designed as a great thread of time, contemplating the following chapters: Before Yesterday that brings the memory of the author and her encounter with others, to get to the object and restlessness of the research; Yesterday that mentions the paths already traveled through the survey by the state of knowledge of dissertations and theses produced with embroidery and teacher training; Today with the possible paths and probable paths presented in this survey and beyond, with the embroidery going through literature, the feminine, ancestry, the construction of research and the formation of being a teacher/researcher, as well as the becoming of this embroidery, plotted and woven together with a cartography built in an embroidered fabric during the process of writing this research; and Tomorrow with the weaving of all these narratives, the reverses, knots and choices of these threads. A qualitative research, anchored in the state of knowledge, being woven throughout its construction by an aesthetic cartography, where the threads woven by the hands through embroidery and writing go through the (re)existence of the teacher training process in an approach for emancipation.
The embroidery-device in the formative processes
Keywords: Formação de Professores; Bordado; Escrita; Educação; Teacher Training; Embroidery; Writing; Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO